The Competency Approach and the Professionalization of Teaching: A Conceptual Clarification - Yves Lenoir; M. Alejandra Morales-Gómez (Universidad Autónoma de Madrid, 2016)
This article seeks to increase conceptual understanding of four questions: Why professionalize the teaching occupation, and what links can be established between professionalization and the competency-based approach? What is meant by competency? What are the contributions of the competency-based approach? What are its limits? The elements presented in the article bring to light the need to ensure an extensive critical reflection in order to make choices that are both difficult and crucial in terms of the production of curricula and their implementation in teaching practices and teacher education practices.